Новий метод зменшення чотирихвильового змiшування, заснований на послабленнi на окремих довжинах хвиль - Abed, Haider J.; Din, N. M.; Al-Mansoori, M. H.; Abdullah, F.; Salim, Noora; Fadhil, Hilal A. (Publishing house "Academperiodika", 2018)
This paper proposes a new method that can suppress the four-wave mixing using an Optical Drop Multiplexing (ODM) technique. The four-wave mixing (FWM) behavior and the performance of wavelength division multiplexing (WDM) systems are investigated, using the proposed technique. It is found that the FWM power is drastically reduced to –96 dBm, when the ODM technique was used. For a WDM system at the first channel (193 THz), the suggested approach offered the bit error rate (BER) to be 1.47*10^-27, in comparison with the absence of the current technique, where BER was 2.53*10^-17. Moreover, it is found that the proposed technique caused the FWM power to reduce by 28 dB.